AI for Selenium Xpath Repair & Maintenance - Ramachandran, Sooraj (International Journal of Computational and Experimental Science and Engineering, 2025)
: In this paper, we explore innovative techniques for repairing and optimizing XPath expressions used in Selenium automation scripts, ensuring greater reliability and maintainability of test cases. Our focus will be on identifying common pitfalls in XPath usage and presenting solutions that enhance the robustness of automated tests, ultimately leading to more efficient testing processes. By employing advanced algorithms and heuristics, we aim to streamline the process of XPath repair, allowing testers to quickly identify and rectify issues that may arise due to changes in the web application's structure. This paper will also discuss the importance of integrating these repair techniques into continuous integration pipelines, enabling teams to maintain high-quality test automation while adapting swiftly to evolving application environments. Integrating these techniques not only improves test resilience but also fosters a culture of proactive quality assurance, where teams can confidently deploy updates without the fear of broken tests undermining their efforts. This proactive approach ultimately leads to more reliable software releases, as teams can focus on innovation and feature development rather than being bogged down by frequent test failures. By prioritizing test automation repair within the development cycle, organizations can enhance collaboration among team members and streamline their workflows, ensuring that quality remains a shared responsibility rather than an afterthought. This shift towards a collaborative quality mindset empowers teams to achieve greater efficiency and responsiveness, ultimately driving business success in a competitive landscape. This transformation not only fosters a culture of accountability but also encourages continuous improvement, as teams learn from past challenges and adapt their processes to better meet evolving customer needs. Embracing this approach allows organizations to not only reduce the time spent on resolving test failures but also to focus on delivering innovative solutions that resonate with their target audience, thereby staying ahead of market trends. By prioritizing quality at every stage of the development process, businesses can enhance customer satisfaction and build long-lasting relationships based on trust and reliability.